Pengaruh perubahan aturan pada hubungan Akrual Diskresioner Positif dan Negatif Terhadap Penundaan Pelaporan Keuangan Perbankan - Desri Yanto; Media Kusumawardani (Politeknik Ganesha Medan, 2026)
ABSTRACT This study examines the impact of regulatory changes on financial reporting delays with earnings management moderated by the COVID-19 pandemic in Indonesia. This quantitative study is based on the study population, namely all 47 banking companies, while the research sample listed on the Indonesia Stock Exchange in 2020-2024 amounted to 35 (175) companies in the research period from 2020 to 2024. This study uses purposive sampling as a data collection method, the data used are the financial statements of banking companies listed on the Indonesia Stock Exchange in 2020-2024. This study uses earnings management variables that use positive and negative earnings management, variables of financial reporting delays, COVID-19 conditions, company size and ROA ratio. The study was tested using multiple regression with SPSS27 test tool, the results of this test indicate that Positive Discretionary Accruals have a positive effect on Financial Reporting Delays, Negative Discretionary Accruals have no effect on Financial Reporting Delays, Positive Discretionary Accruals moderated by the COVID-19 variable have a positive effect on Financial Reporting Delays, and Negative Discretionary Accruals moderated by the COVID-19 variable have no effect on Financial Reporting Delays. The results of the study indicate that the decline in profits during the pandemic is considered normal due to sluggish macroeconomic conditions. Therefore, the interaction between the crisis and negative earnings management does not trigger significant audit delays. Keywords: Banking Company; Financial Reporting Delays; Negative Discretionary Accruals; Positive Discretionary; Accruals;.